TEACHING USING GAMES IN PHYSICAL EDUCATION LESSONS - Z. A. Nazarov (Journals Park Publishing, 2022)
This article provides the necessary information about the development of physical culture of school-aged students in physical education classes, and this thesis is recommended for use as a methodical guide for secondary school teachers.
Keywords: Physical education, games, educational processes, game history, behavior, interpersonal relations, game methods, interesting, innovative method.